Biochar-assisted rapid formation of core–biofilm anammox granules via interfacial trapping of extracellular polymeric substances - Jingwei Fu; Yue Li; Yaqian Liu; Can Xiong; Pei Li; Xuanqi Long; Qian Li; Rong Chen (Bioresource Technology, 2026)

Single-cell transcriptomics reveals heterogeneous stress responses and Mg2+-mediated survival mechanisms in Lactobacillus delbrueckii subsp. bulgaricus during freeze-drying and storage - Liang Liu; Jing Ren; Zhongxia Li; Xinyue Hao; Can Di; Zixin Fu; Liang Li; Xiaolei Ze; Ruikun He; Lanwei Zhang; Pimin Gong (Food Research International, 2026)

Phosphogypsum-derived CaSO4 as a catalyst for NH3-SCR in NOx reduction: A DFT study - Li Zhang; Dingming Ma; Jiliang Yang; Guangxu Yang; Leyuan Cui; Chunyan Li; Can Cui; Yingchun Luo; Lingyun Zhou; Gang Fu (Journal of Environmental Chemical Engineering, 2026)

The effect of adding human Milk phospholipid analogs on the digestive properties of infant formula - Xuanfei Fu; Yue Pan; Shuai Liu; Jiaxuan Gai; Xiaodong Li; Lu Liu; Can Zhang; Jiaqi Hao; Xinyu Du; Bin Zhu (Food Research International, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Corrigendum to ‘The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China’ [Palaeoworld 34 (2025) 200995] - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2026)

Molecular orchestration of highland barley starch-β-glucan complexes under extrusion thermomechanics: linking hierarchical structure to digestive resistance - Liping Fu; Yingting Zhao; Xinyi Chen; Lujie Cheng; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Research International, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

AI-driven protein engineering: A new paradigm for plant trait design - Ran Fu; Shan Jiang; Tianhao Wu; Can Yin; Jun Yan; Xiangfeng Wang (Molecular Plant, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Data-driven optimization of heterogeneous time-of-use pricing for electric vehicle fleets - Zhonglin Fu; Can Cao; Feng Gao (Journal of Cleaner Production, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

A centrifugal speed-based method for controlling debranched products of highland barley amylopectin distribution and isolating long-branched chains - Xinyi Chen; Can Zhao; Yang Liu; Liping Fu; Wenhui Zhang; Qisen Xiang; Yuting Tian; Yingting Zhao (Food Hydrocolloids, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2025)

Effects of high-moisture extrusion technology on structural properties, physicochemical properties and in-vitro starch digestibility of highland barley (Zangqing 3000) flour - Liping Fu; Yingting Zhao; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Chemistry, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Cover Image - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)

Detection and Genomic Characterisation of Scale Drop Disease Virus (SDDV) in Farmed Yellowfin Seabream ( Acanthopagrus latus ) in Southern China - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Scale drop disease virus (SDDV) is a distinct member of the genus Megalocytivirus within the family Iridoviridae , which was recently identified as a causative agent of yellowfin seabream Acanthopagrus latus ascitic diseases (YFSBAD). Here, a molecular surveillance of SDDV in pond‐cultured yellowfin seabream was conducted during 2021 to 2023 in Zhuhai, the most significant breeding region for this fish species in China. A total of 73 batches of naturally diseased yellowfin seabream samples were collected for SDDV detection. As a result, 31 samples were confirmed SDDV positive by conventional PCR detection, among which 9 additional SDDVs were isolated by using MFF‐1 cell line, and 4 isolates were further validated by monoclonal antibody‐based immunofluorescence assays. Multiple alignment and phylogenetic analysis revealed that these isolates shared the identical mcp sequences and were clustered within the same clade. Additionally, the complete genome sequence of a new SDDV isolate (SDDV‐ZH918/23) was determined and annotated. The result shows that SDDV‐ZH918/23 consists of 131,741 bp and encodes 143 putative open reading frames. The genome collinearity analysis demonstrated very high nucleotide similarity among all SDDV isolates distributed in China and other Asian countries. Unexpectedly, a 152 bp deletion mutant was also found in two SDDV isolates. Collectively, our study once again demonstrates that SDDV acts as an emerging etiological agent in farmed yellowfin seabream, and a partial deletion mutant of the SDDV genome was first recorded.

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Research Progress on Genetic Diversity and Molecular Breeding of Onobrychis viciifolia - Can Zhu; Yanchao Zhu; Xiaoyang Sun; Qiang Fu; Feng Yuan; Yinruizhi Li; Jinmin Fu (Plant Molecular Biology Reporter, 2025)

Unraveling the catalytic pyrolysis of oleic acid to produce biodiesel-range hydrocarbon fuel with Ni-loaded Ce-Zr mesoporous catalysts by tuning the crystal face structure - Meihua Fu; Huaiyuan Tang; Jida Wang; Defa Hou; Fulin Yang; Yi Lu; Can Liu; Xu Lin; Zhifeng Zheng; Yunwu Zheng (Fuel, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Recent advancements in observations, sources, and environmental effects of atmospheric hydrogen peroxide (H2O2) - Lian Duan; Shuyuan Jia; Xuran Li; Yalong Wang; Yiming Zhang; Shuang Fu; Yang Wang; Can Ye; Pengfei Liu; Zongbo Shi; Yujing Mu (Atmospheric Environment, 2025)

Exploring the impact of the digital economy on carbon emission intensity: A case study of the urban agglomeration in the middle reaches of the Yangtze River - Tiangui Lv; Can Geng; Shufei Fu; Qiao Zhao; Han Hu; Xinmin Zhang (Environment, Development and Sustainability, 2025)

Current status, problems and promotion strategies of AI application in industrial energy management: A case study from China - Zhong-Lin Fu; Can Cao; Feng Gao (Journal of Cleaner Production, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

Evaluation of the impact of ecological poplar retreat on the net primary productivity of Lake Wetland - Xueke Tian; Yu Huang; Wenmin Hu; Guo Li; Can Li; Ruihan Yang; Chen Fu; Weiqun Lei (Ecological Engineering, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

QTL mapping and candidate gene identification for lower temperature tolerance and growth traits using whole genome re-sequencing in Argopecten scallops - Fu-Kai Wang; Pei-Can Zhu; Xiao-Tong Zhang; Kai Yu; Chun-De Wang; Bo Liu (Aquaculture, 2025)

Effect of biochar on anaerobic co-digestion performance of cellulosic ethanol refinery waste liquor with swine manure - Haoran Li; Sunqiang Xu; Yingyan Liang; Can Fu; Yongxin Pang; Zhantian Tang; Guican Bi; Jun Xie (Journal of Water Process Engineering, 2025)

Highly efficient recovery of gold by thermally modified pyrite and its mechanism - Yuhong Fu; Can Wu; Qin Liu; Shanshan Li; Sen Li; Shuai Zhang; Quan Wan (Minerals Engineering, 2024)

Magnesium isotope constraints on the role of recycled carbonate-rich sediments in the formation of ultrapotassic magmatic rocks at a continental arc setting - Yu Chen; Yi-Xiang Chen; Fatma Gülmez; Ş. Can Genç; Guo-Chao Sun; Zi-Fu Zhao (Lithos, 2024)

Light driven depolymerization of tobacco waste: A multi-scale simulations - Jia-hao Wang; Xian-jie Zhang; Lin-can Fang; Wen-xian Chen; An-Fu Hu; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2024)

DTTR: Encoding and decoding monthly runoff prediction model based on deep temporal attention convolution and multimodal fusion - Wen-chuan Wang; Wei-can Tian; Xiao-xue Hu; Yang-hao Hong; Fu-xin Chai; Dong-mei Xu (Journal of Hydrology, 2024)

Anti-Z-scheme polymer/polymer heterojunctions achieving synchronous enhancement of light absorption and directly spatial charge separation - Yong Li; Xinjia Zhang; Jianhua Zheng; Tianyuan Xiao; Qiu Fu; Can Yang; Dongting Wang; Guoqiang Zhang (Chemical Engineering Journal, 2024)

Effect of inorganic arsenic in paddy soil on the migration and transformation of selenium species in rice plants - Ganga Raj Pokhrel; Kaiteng Wang; Kaiyang Ying; Yongchen Wu; Ze Wang; Xi Zhu; Can Qu; Hong Li; Fengfu Fu; Guidi Yang (Journal of Environmental Sciences, 2024)

Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Fengju Wang; Ruiming Lin; Hongqi Si; Chuanxi Ma; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

In-depth understanding of the synergistic effect in catalytic copyrolysis of lignin-plastic mixtures with lignin-tailored hierarchical HZSM‑5 catalysts - Yifei Chen; Meihua Fu; Jida Wang; Defa Hou; Yi Lu; Fulin Yang; Can Liu; Xu Lin; Zhifeng Zheng; Yunwu Zheng (Fuel, 2024)

Soil microbial community variation in vanadium-enriched farmland surrounding vanadium titanomagnetite tailing in Southwest China - Yunxia Fu; Mingxing Li; Jianpeng Li; Dilin Chen; Tianhui Ye; Can Wang; Fangfang Yan; Zhongping Qiu (Applied Soil Ecology, 2024)

The number of test organisms might influence the toxicity evaluation of hydrophobic micropollutants - Yun Yang; Xiangru Zhang; Longshan Fu; Can Li; Siwei Zhang (Chemosphere, 2024)

Structural/surficial dual regulated granular H2TiO3 lithium-ion sieves for lithium extraction from salt lake brine - Wei Qu; Yuchen Fu; Yunsheng Zhang; Weichao Wang; Chuan Xu; Can Liu; Yun Zhang; Qian Wang; Baicang Liu (Journal of Cleaner Production, 2024)

Potential of combined reactor and static composting applications for the removal of heavy metals and antibiotic resistance genes from chicken manure - Qu Luo; Hu Wang; Xiaoqing Lu; Can Wang; Ruiying Chen; Jianbo Cheng; Tengbing He; Tianling Fu (Journal of Environmental Management, 2024)

Identification of flowering genes in Camellia perpetua by comparative transcriptome analysis - Jing-jing Yu; Jia Cui; Han Huang; Dong-can Cen; Fang Liu; Zeng-Fu Xu; Yi Wang (Functional & Integrative Genomics, 2024)

Insights from CMIP6 SSP scenarios for future characteristics of propagation from meteorological drought to hydrological drought in the Pearl River Basin - Zhaoqiang Zhou; Yibo Ding; Qiang Fu; Can Wang; Yao Wang; Hejiang Cai; Suning Liu; Shengzhi Huang; Haiyun Shi (Science of The Total Environment, 2023)

The effects of earthworm inoculation on cadmium-contaminated rice field in Southern China: a pot experiment and a field test - Yin Zhang; Chunyun Guan; Can Chen; Zhiqiang Fu; Ren Wang; Quan Zhang; Zhengjun Yu; Huang Huang (Environmental Science and Pollution Research, 2023)

Impact of the intensive use of urban construction land on carbon emission efficiency: evidence from the urban agglomeration in the middle reaches of the Yangtze River - Tiangui Lv; Can Geng; Xinmin Zhang; Zeying Li; Han Hu; Shufei Fu (Environmental Science and Pollution Research, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Electrospun Ce–Mn oxide as an efficient catalyst for soot combustion: Ce–Mn synergy, soot-catalyst contact, and catalytic oxidation mechanism - Yuxi Liao; Peng Liu; Jun Zhang; Can Wang; Longwen Chen; Dengfeng Yan; Quanming Ren; Xiaoliang Liang; Mingli Fu; Suib Steven L.; Daiqi Ye (Chemosphere, 2023)

Preparation of nitrogen-containing compounds and nitrogen-doped biochar via nitrogen-rich pyrolysis coupled with ammonia source impregnation - Donghua Li; Meihua Fu; Tao Pei; Yi Lu; Can Liu; Xu Lin; Defa Hou; Hao Sun; Cuiping Luo; Zhifeng Zheng; Yunwu Zheng (Journal of Environmental Chemical Engineering, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Spatiotemporal heterogeneity and decoupling decomposition of industrial carbon emissions in the Yangtze River Delta urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Hualin Xie; Shufei Fu; Can Geng; Zeying Li (Environmental Science and Pollution Research, 2023)

Zinc supplementation ameliorates sorafenib-induced cognitive impairment through ROS/JNK signaling pathway - Can-Can Zhou; Yu-Qiong He; Yu-Shuang Qiu; Chen-Xu Ni; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2023)

Spatiotemporal dynamics and decoupling mechanism of economic growth and carbon emissions in an urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Shufei Fu; Can Geng; Zeying Li (Environmental Monitoring and Assessment, 2022)

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Artemisinin suppresses myocardial ischemia–reperfusion injury via NLRP3 inflammasome mechanism - Fengyue Wang; Qianping Gao; Jing Yang; Can Wang; Junxian Cao; Junfeng Sun; Zhixin Fan; Lu Fu (Molecular and Cellular Biochemistry, 2020)

Increased fes1a thermotolerance is induced by BAG6 knockout - Can Fu; Yanfei Hou; Jingjing Ge; Limin Zhang; Xiaxia Liu; Panfei Huo; Jian Liu (Plant Molecular Biology, 2019)

Agromyces mangrovi sp. nov., a Novel Actinobacterium Isolated from Mangrove Soil - Ruijun Wang; Can Chen; Yue Su; Xiaoyun Yu; Chongya Zhang; Geyi Fu; Shuaibo Han; Xianmao Pan; Junming Qiu; Xiaopin Li; Min Wu (Current Microbiology, 2018)

Traditional symbiotic farming technology in China promotes the sustainability of a flooded rice production system - Huabin Zheng; Huang Huang; Can Chen; Zhiqiang Fu; Huaqin Xu; Shuduan Tan; Wei She; Xiaolan Liao; Jianwu Tang (Sustainability Science, 2017)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Phosphate adsorption on uncoated and humic acid-coated iron oxides - Hui Wang; Jun Zhu; Qingling Fu; Can Hong; Hongqing Hu; Antonio Violante (Journal of Soils and Sediments, 2016)

The involvement of TsFtsH8 in Thellungiella salsuginea tolerance to cold and high light stresses - Xia Xia Liu; Can Fu; Wen Wen Yang; Quan Zhang; Hai Fan; Jian Liu (Acta Physiologiae Plantarum, 2016)

AtFes1A is essential for highly efficient molecular chaperone function in Arabidopsis - Can Fu; Jingxia Zhang; Xiaxia Liu; Wenwen Yang; Hongbin Yu; Jian Liu (Journal of Plant Biology, 2015)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

Essential oil of Actinidia macrosperma, a catnip response kiwi endemic to China - Yun-peng Zhao; Xiao-yun Wang; Zhi-can Wang; Yin Lu; Cheng-xin Fu; Shao-yuan Chen (Journal of Zhejiang University-SCIENCE B, 2006)